Kompetensi Sumber Daya Manusia Dan Kualitas Laporan Keuangan Pemerintah Daerah: Peran Sistem Pengendalian Internal Sebagai Pemediasi - Evi Rahmawati; Sari Sonita; Arif Wahyu Nur Kholid; Hafiez Sofyani (Jurnal Reviu Akuntansi dan Keuangan, 2022)
The study aims to examine the effect of the internal control systems as mediating variable in influencing competence of human resource on the quality of financial statement. This is quantitative study that used a questionnaire survey. The subject of this study is Local Government Organizations (LGO) located in Yogyakarta City. Hypotheses testing was conducted by employing Structural Equation Modelling-Partial Leas Square (SEM-PLS) technique. This study revealed that the competence of human resource and internal control system have positive effect on the quality of financial statement of LGOs. In addition, internal control system mediated the relationship between competence of human resource and the quality of Local Government Organizations financial statement. The implications of this study are the local government must maintain and improve the competence of human resources through education and training, thus the internal control system will be encouraged, and the quality of Local Government Organizations financial statement will enhance.